Use of oscillometric devices in atrial fibrillation: a comparison of three devices and invasive blood pressure measurement. (2nd January 2018) - Halfon, Matthieu; Wuerzner, Gregoire; Marques-Vidal, Pedro; Taffe, Patrick; Vaucher, Julien; Waeber, Bernard; Liaudet, Lucas; Ltaief, Zied; Popov, Milen; Waeber, Gerard
Abstract: Background: The use of automated (oscillometric) blood pressure (BP) devices is not validated in atrial fibrillation (AF) patients. Objectives: To assess the reliability of three oscillometric BP devices, and the agreement with invasive arterial blood pressure(IBP) in AF patients. Methods: 48 AF patients with randomized sequences of 10 consecutive BP measurements with two pairs of devices: (1) OmronR7™(wrist) and OmronHEM907™(arm); (2) OmronR7™ and Microlife WatchBPhome(arm). Reliability and agreement of each device were assessed by the intra-class correlation coefficient (ICC) for the continuous BP measurements and Bland & Altman methodology, respectively. In 10 additional AF patients, 10 consecutive measurements with IBP and OmronHEM907™, and IBP and Microlife WatchBPhome were performed. Results: The OmronR7™ was not able to obtain any BP Readings. Arm devices presented better ICC for systolicBP(SBP) than for diastolicBP(DBP) (Omron HEM907™:0.94 [0.90; 0.97] vs. 0.77 [0.67; 0.89]; Microlife WatchBPhome:0.92 [0.88; 0.96] vs.0.79 [0.69; 0.89]).The correlation coefficient between Microlife WatchBPhome and IBP computed using the average of repeated measurements from two to ten measurements improved up to the third and remained stable afterwards. The agreement between IBP and SBP, and IBP and DBP, was moderate as illustrated by a wide limit of agreement [−24; 26](SBP) and [−15;17](DBP) for Microlife WatchBPHome, respectively and [−30; 13](SBP) and [−7; 15](DBP) for OmronHEM907. Conclusions: BP measurement using the two arm oscillometric devices achieved a high reliability for SBP. The agreement between IBP and arm devices was low but using the average of three consecutive measurements improved the results substantially.